Service quality from the perspective of myocardial infarction patients - Kamal Gholipour; Jafar Sadegh Tabrizi; Solmaz Azimzadeh; Samad Ghafari; Shabnam Iezadi (KARE Publishing, 2018)
Objective: Service quality (SQ) generally refers to the non-clinical aspects of health services and primarily focuses on the relationship between the care provider and the customers, and the environment in which care services are delivered. The aim of this study was to assess the SQ provided for myocardial infarction (MI) from the patients' perspective. Methods: A cross-sectional study was conducted with 164 patients with MI at the Tabriz Shahid Madani cardiology clinic. Study participants were selected using convenience sampling. SQ was measured using a validated Comprehensive Quality Measurement in Healthcare SQ questionnaire. The reliability was confirmed based on Cronbach's alpha coefficient (α=0.81). SQ was calculated using the formula SQ=10-(importance × performance), based on the importance and performance of non-health-related aspects from the customers' perspective. Importance scores ranged from 1 to 10 and performance was scored between 0 and 1. Results: Of 164 participants, about 75% were men and almost 44% were between 51 and 65 years of age. From the customers' perspective, the total SQ score was 6.80 (0-10 scale), and the individual scores for all SQ aspects were below an acceptable level. Confidentiality, dignity and continuity were given the highest scores, while availability of support groups had the lowest score. Conclusion: The study findings revealed an opportunity to improve SQ. Patient and provider participation in quality improvement activities could be an effective strategy to improve the aspects of health care quality that were most important to the customers and those with low scores, such as availability of support groups.